Perceptual, Aerodynamic and Acoustic Evaluation of Vocal Characteristics in Subjects With Obesity - Munjal, Sanjay; Sharma, Anuradha; Chhabra, Neha; Panda, Naresh (Journal of voice, 2024)
Obesity has tripled since 1975 and affects health across many domains. Increasing body mass index increases the risk to the obese subject of many non-communicable diseases. The study evaluated the perceptive, aerodynamic, and acoustic parameters that characterize the voice of the obese population. Eighty adult subjects (40 participants in each obese and control group) aged 18-50 years were enrolled. The perceptual voice analysis was performed using the Consensus Auditory Perceptual Evaluation of Voice. The aerodynamic and acoustic voice analyses were performed using the MIR Spiro lab instrument and Doctor's Speech software. A digital stopwatch was also used to measure maximum phonation time. Statistical analysis revealed a significant difference (P-value <0.05 and t value >2) between two groups on acoustic parameters, specifically Normalized noise energy and fundamental frequency tremor (F0 tremor). Normalized noise energy and fundamental frequency tremor were greater in the obese group. Moreover, maximum phonation time and expiratory reserve volume were significantly reduced in the obese group. Results of the present study showed poor voice quality and reduced expiratory reserve volume in obese individuals. This could be credited to the adverse effects of accrued adipose on the functioning of the laryngeal and respiratory systems. Increasing body mass index escalates the risk to the obese subjects of many non-communicable diseases.